Estimating causal effects of genetically predicted type 2 diabetes on COVID-19 in the East Asian population - Yoshikawa, Masahiro; Asaba, Kensuke; Nakayama, Tomohiro (Frontiers in Endocrinology, 2022)
Background: Observational studies suggested that type 2 diabetes mellitus (T2DM) was associated with increased risk of coronavirus disease 2019 (COVID-19). However, Mendelian randomization (MR) studies in the European population failed to find causal associations partly because T2DM was pleiotropically associated with body mass index (BMI). We aimed to estimate causal effects of T2DM on COVID-19 outcomes in the East Asian (EAS) population using two-sample MR approach. Methods: We obtained summary statistics from a genome-wide association study (GWAS) that included 433,540 EAS participants as the exposure dataset for T2DM risk and from COVID-19 Host Genetics Initiative GWAS meta-analyses (round 7) of EAS ancestry as the outcome dataset for COVID-19 susceptibility (4,459 cases and 36,121 controls), hospitalization (2,882 cases and 31,200 controls), and severity (794 cases and 4,862 controls). As a main MR analysis, we performed the inverse variance weighted (IVW) method. Moreover, we conducted a series of sensitivity analyses including IVW multivariable MR using summary statistics for BMI from a GWAS with 158,284 Japanese individuals as a covariate. Results: The IVW method showed that the risk of T2DM significantly increased the risk of COVID-19 susceptibility (odds ratio [OR] per log (OR) increase in T2DM, 1.11; 95% confidence interval [CI], 1.02-1.20; P = 0.014) and hospitalization (OR, 1.15; 95% CI, 1.04-1.26; P = 0.005) although the risk of severity was only suggestive. Moreover, IVW multivariable MR analysis indicated that the causal effects of T2DM on COVID-19 outcomes were independent of the effect of BMI. Conclusions: Our MR study indicated for the first time that genetically predicted T2DM is a risk factor of SARS-CoV-2 infection and hospitalized COVID-19 independent of obesity in the EAS population.